Roux‐en‐Y gastric bypass for super obese patients: what approach?. Issue 2 (19th April 2015) - Buchs, Nicolas C.; Azagury, Dan E.; Pugin, François; Jung, Minoa K.; Huber, Olivier; Chassot, Gilles; Morel, Philippe
Abstract: Background: Super obese (SO) patients with a Body Mass Index (BMI) ≥ 50 kg/m 2 still represent a real anesthesiological and surgical challenge. While the best procedure to perform in this population remains unclear, robotic technology has been proposed to accomplish Roux‐en‐Y gastric bypass (RYGB). The study aim is to report our experience of robotic RYGB for SO patients and to compare it with open and laparoscopic surgery. Methods: From July 1997 to March 2014, all consecutive RYGB cases for SO patients were collected in a dedicated database and reviewed retrospectively. Two hundred and fourteen SO patients were operated on: 65 by a robotic approach (30.4%), 54 by a laparoscopic approach (25.2%), and 95 using an open approach (44.4%). Peri‐ and post‐operative data were compared between the three approaches. Results: There were more male patients in the robotic group, but with a slightly lower BMI. The operative time was longer for the robotic (+27 min) and laparoscopic (+21 min) groups in comparison with the open group ( P < 0.05). Overall, there were less reoperations ( P < 0.05) and a shorter hospital stay ( P < 0.05) in the robotic group in comparison with other groups. Of note there was also a trend in favor of robotics with less conversions ( P = 0.08) and less postoperative complications ( P ≥ 0.05). Conclusions: Robotic RYGB can be performed safely in super obese patients with results that compare favorably with laparoscopic and open surgery. However, the robotic approach has a longer operative time. The exact role of robotics for super obese population needs to be clarified in larger and randomized trials before drawing definitive conclusions. Copyright © 2015 John Wiley & Sons, Ltd.